ESPOSITO DAN KAPITALISME DI BUMI ISLAM Kajian Hak Milik Pribadi, Privatisasi dan Intervensi Negara, serta Kesenjangan Buruh-Majikan - Maghfur Ahmad (JURNAL PENELITIAN, 2014)
This research study Esposito views about Islam's rejection of capitalism. Background of this study is his book What Everyone Needs to Know About Islam, section "why does Islam reject capitalism?". Given the very broad spectrum of topics capitalism, then this study focused on the key issues of private property rights, privatization and state intervention and worker-employer gap Islamic perspective . Research literature indicates that Islam is a middle way between capitalism and socialism. Capitalism recognizes private property without limit, Islam restrict individual ownership, collective ownership of resources is not guaranteed and exclusive ownership. Principle of capitalism are competition, free markets and individual competition without limits, Islam allows the state to intervene economic, market and business, in order to keep harmony, continuity and shared prosperity. Therefore, Islam recognizes the principle of property rights of rich people on poor people. There is the social responsibility of the state, rich people, and the employer, capitalism does not require otherwise.